Three-dimensional porous carbon material, preparation method and application of three-dimensional porous carbon material in adsorption of organic pollutants in water body
By synthesizing three-dimensional porous carbon materials using zinc salt, 2-methylimidazole and nitrogen sources, the existing adsorbents are solved in the slow speed of removing organic pollutants in water and are susceptible to the chemical composition of the solution, achieving efficient and anti-interference adsorption effect of organic pollutants, and avoiding the risk of secondary pollution of metal ions dissolution.
Patent Information
- Application Number
- CN202411962183.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-04
AI Technical Summary
When existing adsorbents remove organic pollutants in water, the adsorption rate is slow, the solution chemical composition has an impact on the removal effect, and the removal efficiency of some organic pollutants is low, and there is a potential secondary pollution risk for metal ions dissolution.
Zinc salt, 2-methylimidazole and nitrogen source are used as the raw materials and structural regulators of the framework material. The precursor zeolite imidazole ester skeleton structural material is synthesized by self-assembly and pyrolyzed under the protection of inert gas to prepare three-dimensional porous carbon material for adsorption of organic pollutants in water.
The prepared three-dimensional porous carbon materials have a large specific surface area, a developed pore structure, and rich nitrogen-containing functional groups. They significantly improve the adsorption performance and anti-interference ability of organic pollutants, and avoid the risk of secondary pollution of metal ions dissolution.
Smart Images

Figure CN119549115A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of water treatment and relates to an adsorption material, in particular to a three-dimensional porous carbon material and a preparation method thereof, and application in adsorbing organic pollutants in water. Background Art
[0002] In recent years, due to the rapid development of industry and the low reuse rate of water, the discharge of chemical wastewater has been increasing, resulting in increasingly serious water pollution problems. As raw materials and intermediate products in the chemical production process, the types and quantities of organic matter entering the water environment are also increasing sharply. Most organic matter is toxic and easily bioaccumulated. Some organic matter also has the "three-hazard" effects of teratogenicity, carcinogenicity, and mutagenicity, which poses great potential hazards to human health and the ecological environment. With the continuous enhancement of people's environmental awareness and the continuous improvement of analytical and detection technology, organic pollution in the water environment has also attracted widespread attention. Therefore, it is imperative to develop technologies to reduce organic pollution in the water environment.
[0003] Adsorption is a treatment technology for efficiently removing organic pollutants from water. Commonly used adsorbents include carbon-based materials (activated carbon, biochar and cellulose, etc.), inorganic minerals (iron minerals, hydrotalcite, etc.), ion exchange resins and polymers (metal organic framework (MOF) polymers and covalent organic framework (COF) polymers). However, the adsorption rate of existing adsorbents is slow (usually taking several hours to tens of hours), the chemical composition of the solution (such as pH, coexisting ions and organic matter) has a great influence on the removal effect of organic pollutants, and the removal efficiency of some organic pollutants (such as short-chain perfluorinated compounds) is low. Therefore, it is necessary to modify the existing adsorbent materials to improve their adsorption performance and enhance their anti-interference ability to the chemical composition of the solution. At present, the commonly used methods for modifying adsorbents for organic pollutants in water bodies mainly include two aspects: first, by increasing the specific surface area and adjusting the pore structure to increase the number of adsorption sites and improve the accessibility to organic pollutants; second, introducing functional groups that are pro-organic pollutants to enhance electrostatic attraction and hydrogen bonding.
[0004] Metal-organic framework polymers are coordination polymers formed by self-assembly of metal ions / clusters and organic bridging ligands. They are widely used three-dimensional porous materials with advantages such as large specific surface area, high porosity, simple synthesis method and adjustable structure. By adjusting the type of metal ions, organic ligands and solvents, the particle size and pore structure of polymer materials can be adjusted. Although metal-organic framework polymers have been used in water treatment, their morphology and structure are relatively simple, their adsorption capacity is limited, and there is a potential risk of secondary pollution due to the dissolution of metal ions. Summary of the invention
[0005] The present invention provides a three-dimensional porous carbon material and a preparation method thereof, and application of the material in adsorbing organic pollutants in water, so as to overcome the defects of the prior art.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] In the first aspect, the present invention provides a method for preparing a three-dimensional porous carbon material, comprising the following steps: step 1, dissolving a zinc salt, 2-methylimidazole and a nitrogen source in a methanol solution respectively, mixing and reacting at room temperature, standing and collecting a precipitate to obtain a precursor zeolite imidazolate skeleton structure material; step 2, pyrolyzing the precursor zeolite imidazolate skeleton structure material at 1100°C under the protection of an inert gas to obtain a three-dimensional porous carbon material.
[0008] Furthermore, in step 1, the zinc salt is one or more of zinc acetylacetonate (Zn(C5H7O2)2), zinc acetate (Zn(CH3COO)2), zinc nitrate hexahydrate (Zn(NO3)2·6H2O), and zinc sulfate (ZnSO4).
[0009] Furthermore, in step 1, the nitrogen source is one or more of melamine (C3H6N6), ammonium chloride (NH4Cl), and dicyandiamide (C2H4N4).
[0010] Furthermore, in step 1, the molar ratio of the zinc salt to 2-methylimidazole is 1:4-16; the molar ratio of the nitrogen source to 2-methylimidazole is 1:10-20.
[0011] Furthermore, in step 1, the reaction time is 1 to 3 hours; and the standing time is 12 to 24 hours.
[0012] Furthermore, in step one, after standing, the precipitate is centrifuged, washed and dried to obtain the precursor zeolite imidazolate framework material; the centrifugal speed is 8000-10000 rpm, and the centrifugal time is 10-20 min; it is washed with methanol 3-5 times; and it is vacuum dried at 60-80°C.
[0013] Furthermore, in step 2, the inert gas is nitrogen (N2) or argon (Ar); the pyrolysis time is 2 to 3 hours, and the pyrolysis heating rate is 5 to 10°C / min.
[0014] In a second aspect, the present invention provides a three-dimensional porous carbon material obtained by the above-mentioned preparation method.
[0015] In a third aspect, the present invention provides the use of the above three-dimensional porous carbon material in adsorbing organic pollutants in water.
[0016] Furthermore, the organic pollutants are one or more of perfluorinated compounds with different carbon chain lengths, benzene series (such as benzene), and chlorinated organic compounds (such as p-chloroaniline).
[0017] The present invention first uses zinc salt and imidazole salt as skeleton material raw materials, and nitrogen source as structure regulator and reducing agent to self-assemble and synthesize precursor zeolite imidazole ester skeleton structure material; then, directly pyrolyze the precursor to evaporate Zn element, obtain NC connected three-dimensional porous carbon material, and apply the prepared three-dimensional porous carbon material to the adsorption and removal of organic pollutants in water. During the precursor synthesis process, the addition of nitrogen sources such as melamine can control crystal growth and obtain a more uniform precursor crystal structure; the nitrogen vacancies in the NC part will rebuild the local coordination environment of the precursor, optimize the Zn-N4 coordination form and enrich the material pore structure in the precursor zeolite imidazole ester skeleton structure material, adjust the band gap width to change the charge density and conductivity, and affect the charge distribution of nearby carbon atoms. During the pyrolysis process, the addition of nitrogen source promotes the formation of more nitrogen-containing functional groups, prevents the aggregation of metals and the collapse of carbon structure during calcination, enhances the stability of the pore structure in the carbonization reaction, and the pyrrole N formed in the three-dimensional porous carbon material can be used as an adsorption site for organic pollutant molecules. At the same time, since the boiling point of the Zn element is 907°C, the Zn in the precursor zeolite imidazolate framework structure material is almost completely volatilized at 1100°C, and the Zn-N4 structure in the precursor zeolite imidazolate framework structure material is reduced to Zn and volatilizes and decomposes, promoting the formation of a developed pore structure, thereby obtaining a three-dimensional porous carbon material with a low metal content, which can effectively avoid the potential secondary pollution risk caused by the dissolution of metal ions during use.
[0018] The beneficial effects of the present invention are:
[0019] The three-dimensional porous carbon material prepared by the present invention has the advantages of large specific surface area, developed pore structure, rich nitrogen-containing functional groups and reusability. It exhibits excellent adsorption performance for emerging organic pollutants in water bodies such as perfluorocarboxylic acids with carbon chain lengths of C4 to C9, traditional organic pollutants such as benzene and p-chloroaniline, as well as various organic pollutants such as perfluorinated compounds, benzene series (such as benzene) and chlorinated organic compounds (such as p-chloroaniline). Specifically, 1100°C pyrolysis can increase the specific surface area and pore volume (especially mesopore volume) of the three-dimensional porous carbon material, increase the number of adsorption sites, accelerate the mass transfer rate and improve the accessibility of organic pollutants; at the same time, the three-dimensional porous carbon material obtained by nitrogen source doping contains uniformly distributed N heteroatoms, especially the nitrogen-containing functional groups such as pyrrole N, which change the electrostatic potential distribution on the surface of the carbon material, promote electron transfer, enhance electrostatic attraction and hydrogen bonding, thereby improving its adsorption performance for organic pollutants. Compared with traditional adsorbents, the three-dimensional porous carbon material prepared by the present invention has a fast adsorption rate and large adsorption capacity for pollutants. For one or more perfluorinated compounds, benzene series and chlorinated organic matter in water bodies, its adsorption efficiency is basically not affected by the chemical composition of the solution (including pH, coexisting ions and organic matter). It has broad application prospects in the field of polluted water remediation, and the material exhibits excellent adsorption and removal performance and anti-interference ability for organic pollutants in water bodies. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 is the N2 adsorption-desorption isotherm (a) and pore size distribution (b) of the three-dimensional porous carbon material of Example 1;
[0021] Figure 2 is the adsorption kinetic curve of PFOA by the precursor zeolite imidazolate framework structure material and the three-dimensional porous carbon material in Example 1;
[0022] Figure 3 is a scanning electron microscope image (a) and an element scanning image (b) of the three-dimensional porous carbon material of Example 2;
[0023] Figure 4 It is a bar graph of the removal effect of the three-dimensional porous carbon material in Example 2 on perfluorinated compounds PFCA (C4-C9), benzene and p-chloroaniline (PCA) with different carbon chain lengths;
[0024] Figure 5 This is a bar graph showing the removal effect of PFOA by the three-dimensional porous carbon material under different solution chemical conditions in Example 3. DETAILED DESCRIPTION
[0025] The present invention is further described below in conjunction with specific embodiments.
[0026] Example 1
[0027] This embodiment provides a three-dimensional porous carbon material for adsorbing organic pollutants in water, and the preparation method thereof comprises the following steps:
[0028] Step 1: Dissolve 1.7 g (5.7 mmol) of zinc nitrate hexahydrate, 3.7 g (45.2 mmol) of 2-methylimidazole and 0.57 g (4.5 mmol) of melamine in 20 mL, 60 mL and 10 mL of methanol solution respectively, quickly mix the three and stir at room temperature for 1 h, let stand and precipitate for 24 h, centrifuge the solid product (9000 rpm, 15 min), wash with methanol 3 times, and finally vacuum dry at 60 ° C to obtain a precursor zeolite imidazole ester framework material.
[0029] Step 2: Place the precursor zeolite imidazolate framework structure material in a tubular furnace and directly pyrolyze it under the protection of nitrogen at a heating rate of 5°C / min, a pyrolysis temperature of 1100°C, and a holding time of 3h to obtain a three-dimensional porous carbon material.
[0030] like Figure 1 As shown in Table 1, the N2 adsorption-desorption isotherms of the three-dimensional porous carbon materials prepared by pyrolysis at 1100°C all conform to the type I isotherm, indicating that a developed microporous structure has been formed, and the pore size is mainly distributed in the range of 0.4 to 2.0 nm. At the same time, there is also 45.90% of mesoporous structure in the three-dimensional porous carbon materials prepared by pyrolysis at 1100°C. The mesoporous structure is more conducive to the rapid entry and diffusion of pollutants into the pores, thereby improving the adsorption rate and adsorption capacity. The specific surface area and pore volume (including micropore volume and mesopore volume) of the three-dimensional porous carbon materials prepared by pyrolysis at 1100°C are significantly increased compared with conventional carbon materials. The larger specific surface area and richer pore structure help to increase the number of adsorption sites, accelerate the mass transfer rate and improve the accessibility of organic pollutants.
[0031] Table 1 Pore structure parameters of three-dimensional porous carbon materials prepared by pyrolysis at 1100℃
[0032]
[0033] The three-dimensional porous carbon material was used to adsorb perfluorooctanoic acid (PFOA) in water. The specific application method was as follows: 0.1 g / L of the three-dimensional porous carbon material was added to a solution with an initial PFOA concentration of 10 mg / L, and the adsorption reaction was carried out in a shaker. Samples were taken at 1, 3, 5, 10, 20, 30, 60, 90, 120 and 240 min, and the removal efficiency of PFOA at different reaction times was calculated. The results are shown in Figure 2. Figure 2 shown.
[0034] The results show that three-dimensional porous carbon materials can achieve efficient removal of PFOA in water, and can reach adsorption equilibrium within 10 minutes; in the equilibrium stage, the removal efficiency of PFOA by three-dimensional porous carbon materials reaches 99.66%. Compared with the precursor zeolite imidazolate framework structure material, the adsorption capacity of PFOA by three-dimensional porous carbon materials prepared by 1100℃ pyrolysis is significantly increased by about 2.8 times.
[0035] Example 2
[0036] This embodiment provides a three-dimensional porous carbon material for adsorbing organic pollutants in water, and the preparation method thereof comprises the following steps:
[0037] Step 1: Dissolve 1.3 g (5.7 mmol) of zinc acetate, 3.7 g (45.2 mmol) of 2-methylimidazole and 0.16 g (3.0 mmol) of ammonium chloride in 23 mL, 69 mL and 8 mL of methanol solution, respectively. Mix the three quickly and stir at room temperature for 1 h. Let it stand for 24 h. Centrifuge the solid product (9000 rpm, 15 min), wash it with methanol 3 times, and finally dry it in vacuum at 60 ° C to obtain a precursor zeolite imidazole ester framework material.
[0038] Step 2: Place the precursor zeolite imidazolate framework structure material in a tubular furnace and directly pyrolyze it under the protection of argon at a heating rate of 5°C / min, a pyrolysis temperature of 1100°C, and a holding time of 3h to obtain a three-dimensional porous carbon material.
[0039] The morphology, structure and element distribution of the three-dimensional porous carbon material are shown in Figure 2. Figure 3 After pyrolysis at 1100 °C, the three-dimensional porous carbon material tends to be more spherical, the surface of the material is rough, the C, N and O elements are evenly distributed on the surface of the material, and the Zn element is almost completely volatilized.
[0040] The three-dimensional porous carbon material is used to adsorb perfluorocarboxylic acid (PFCA), benzene and p-chloroaniline (PCA) with different carbon chain lengths in water. The specific application method is as follows: 0.1 g / L of the three-dimensional porous carbon material is added to a solution with an initial concentration of 10 mg / L of PFCA, Benzene and PCA, and the adsorption reaction is carried out in a shaker for 2 hours. The concentrations of PFCA, Benzene and PCA in the solution are sampled and tested, and the removal efficiency of PFCA, Benzene and PCA is calculated. The results are shown in FIG. Figure 4 shown.
[0041] The results show that the three-dimensional porous carbon material exhibits good adsorption performance for PFCAs with different carbon chain lengths (C4-C9) in water. The PFCA removal efficiency is from high to low, and the order is perfluorononanoic acid (PFNA, 99.83%) > perfluorooctanoic acid (PFOA, 99.70%) > perfluoroheptanoic acid (PFHpA, 99.16%) > perfluorohexanoic acid (PFHxA, 98.54%) > perfluoropentanoic acid (PFPeA, 88.44%) > perfluorobutyric acid (PFBA, 72.58%). After adsorption, the removal efficiencies of benzene and p-chloroaniline are 94.97% and 96.08%, respectively.
[0042] Example 3
[0043] This embodiment provides a three-dimensional porous carbon material for adsorbing organic pollutants in water, and the preparation method thereof comprises the following steps:
[0044] Step 1: Dissolve 1.7 g (5.7 mmol) of zinc nitrate hexahydrate, 1.9 g (22.6 mmol) of 2-methylimidazole and 0.19 g (2.3 mmol) of dicyandiamide in 18 mL, 52 mL and 7 mL of methanol solution respectively, quickly mix the three, stir at room temperature for 1 hour, let stand for 24 hours, centrifuge the solid product (9000 rpm, 15 min), wash with methanol 3 times, and finally vacuum dry at 60°C to obtain a precursor zeolite imidazole ester framework material;
[0045] Step 2: Place the precursor zeolite imidazolate framework structure material in a tubular furnace and directly pyrolyze it under the protection of nitrogen at a heating rate of 10°C / min, a pyrolysis temperature of 1100°C, and a holding time of 2h to obtain a three-dimensional porous carbon material.
[0046] The three-dimensional porous carbon material was used to adsorb perfluorooctanoic acid (PFOA) in water. The specific application method was as follows: 0.1 g / L of the three-dimensional porous carbon material was added to a solution with an initial PFOA concentration of 10 mg / L, the initial pH of the solution was adjusted to 3, 5, 7, 9 and 11, or additional NaCl, NaNO3, Na2CO3, Na2SO4 and humic acid (HA, representative organic matter) were added, and the adsorption reaction was carried out in a shaker for 2 hours. The PFOA concentration in the solution was sampled and tested, and the removal efficiency of PFOA was calculated. The results are shown in FIG. Figure 5 shown.
[0047] The results show that in a wide pH range (3-11), the three-dimensional porous carbon material exhibits excellent adsorption performance for PFOA, and the removal efficiency remains above 98%. 2- 、CO3 2- and SO4 2-Plasma and HA hardly inhibit the adsorption of PFOA by the three-dimensional porous carbon material, and the PFOA removal efficiency remains above 90%.
[0048] The used three-dimensional porous carbon material was collected and placed in a methanol / sodium chloride composite solution for desorption. The desorbed three-dimensional porous carbon material was used again to adsorb PFOA. The results are shown in Table 2.
[0049] Table 2 PFOA adsorption and recycling performance of three-dimensional porous carbon materials prepared by pyrolysis at 1100℃
[0050] Loop 1 Loop 2 Loop 3 Loop 4 Loop 5 Removal rate 99.37% 96.91% 94.02% 89.71% 85.91%
[0051] The results show that after five adsorption-desorption cycles, the adsorption removal rate of PFOA by the three-dimensional porous carbon material still reaches 85.91%. The reuse experiment shows that the three-dimensional porous carbon material prepared by the present invention has good reuse performance.
[0052] In the present invention, unless otherwise specified, the scientific and technical terms used herein have the meanings commonly understood by those skilled in the art. In addition, the reagents, materials and operating procedures used herein are reagents, materials and conventional procedures widely used in the corresponding fields.
[0053] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a three-dimensional porous carbon material, characterized in that: The following steps are involved: Step 1: Dissolve the zinc salt, 2-methylimidazole and nitrogen source in methanol solution respectively, mix them, stir and react at room temperature, and let them stand to collect precipitation to obtain a precursor zeolite imidazole ester framework structure material; Step 2: pyrolyze the precursor zeolite imidazolate framework material at 1100° C. under the protection of an inert gas to obtain a three-dimensional porous carbon material.
2. The method for preparing a three-dimensional porous carbon material according to claim 1, characterized in that: In step 1, the zinc salt is one or more of zinc acetylacetonate, zinc acetate, zinc nitrate hexahydrate, and zinc sulfate.
3. The method for preparing a three-dimensional porous carbon material according to claim 1, characterized in that: In step 1, the nitrogen source is one or more of melamine, ammonium chloride and dicyandiamide.
4. The method for preparing a three-dimensional porous carbon material according to claim 1, characterized in that: In step 1, the molar ratio of the zinc salt to 2-methylimidazole is 1:4-16; The molar ratio of the nitrogen source to 2-methylimidazole is 1:10-20.
5. The method for preparing a three-dimensional porous carbon material according to claim 1, characterized in that: In step 1, the reaction time is 1 to 3 hours; the standing time is 12 to 24 hours.
6. The method for preparing a three-dimensional porous carbon material according to claim 1, characterized in that: In step 1, after standing, the precipitate is centrifuged, washed, and dried to obtain the precursor zeolite imidazolate framework structure material; The speed of centrifugal separation is 8000-10000 rpm, and the centrifugal time is 10-20 min; Wash with methanol 3 to 5 times; Vacuum drying at 60-80°C.
7. The method for preparing a three-dimensional porous carbon material according to claim 1, characterized in that: In step 2, the inert gas is nitrogen or argon; The pyrolysis time is 2 to 3 hours, and the pyrolysis heating rate is 5 to 10°C / min.
8. A three-dimensional porous carbon material obtained by the preparation method according to any one of claims 1 to 7.
9. Use of the three-dimensional porous carbon material as claimed in claim 8 in adsorbing organic pollutants in water.
10. The use of the three-dimensional porous carbon material according to claim 9 in adsorbing organic pollutants in water, characterized in that: The organic pollutants are one or more of perfluorinated compounds, benzene series, and chlorinated organic compounds with different carbon chain lengths.
Citation Information
Cited By
Porous hydrophobic carbon material as well as preparation method and application thereof
CN121158779A